Utilizing the RE-AIM framework for a multispecialty Veterans Affairs Extension for Community Healthcare Outcomes (VA-ECHO) program 2018–2022 - Mattox, Elizabeth A.; Yantsides, Konstantina E.; Germani, Maureen Wylie; Parsons, Elizabeth C. (Frontiers in Health Services, 2023)
VA-ECHO (Veterans Affairs -Extension for Community Healthcare Outcomes) provides live, synchronous, continuing education accredited, case-based learning. Sessions deliver up-to-date, evidence-based, practice-relevant, Veteran-focused learning to healthcare team members. The primary goal of VA-ECHO is to increase Veterans' access to high quality care by improving knowledge and skills among VA care providers. Utilizing the RE-AIM framework, descriptive statistics for 23 VA-ECHO programs regarding program effectiveness, adoption, implementation, and maintenance during a five-year period (2018–2022) are reported. VA-ECHO offered 1,462 sessions and 157,238 contact hours, engaging 17,642 participants from 837 VA-based sites (20% rural-based sites). Effectiveness includes information on number and diversity of programs, as well as reported impact on participants' practice. Adoption includes descriptive statistics, including comparison of growth and change compared to prior years. Implementation describes change in the program over time, including the number of specialties offered, and types of continuing education offered. Maintenance includes a narrative regarding sustainability. The discussion focuses on implementation and maintenance strategies the program has used to address participant and VA needs within the RE-AIM framework, including adjustments to the program, iterative qualitative improvement, sustainment strategies, and opportunities for future evaluation.